Innovative Green Technology for Sustainable Industrial Estate Development - Hadiwijoyo, R.; Purwanto, P.; Hadi, Sudharto P. (Center of Biomass & Renewable Energy, Diponegoro University, 2013)
Sustainable industrial development requires a balance between economic growth,equity and environment. Two major components of industrial development are energy and rawmaterials. To minimize the environmental impacts of energy and raw materials, important stepsare required to deal with the green economy and global warming issues. The use of innovationtechnology to industrial gas emission is a preventive solution facing global warming. A research hasbeen done in Industrial Estate in Cilegon (IEC) Banten province, Indonesia, to see how to reduceenergy demand and encourage uses of more environmentally-friendly energy in the estate. Fossilenergy needs in the industrial estate were analyzed to see the opportunities of energy saving andrenewable energy development. The target to be achieved is to reduce the greenhouse gasemissions and improve the energy efficiency in the industrial park.